VALUASI EKONOMI MITIGASI LAHAN PERTANIAN RAWAN BANJIR - Darwati Darwati (Universitas Muhammadiyah Yogyakarta, 2015)
Abstract: The purpose of this study is to identify the location of flood prone areas, determine the economic value of agricultural land prone to flooding mitigation, and determine the factors that influence the Willingness To Pay (WTP) mitigation of flood-prone farmland in Purworejo.The data used is primary data is done by direct interview to the respondents. The sampling technique by using simple random sampling. The sample in this study were 81 farmers in the village Kedungmulyo. Analysis of data using Geographic Information Systems (GIS), Contingent Valuation Method (CVM) and multiple linear regression. The results of this study indicate that almost all districts in the flood-prone Purworejo except District of Bruno and the District Kaligesing. The average willingness to pay for mitigation of flood-prone agricultural land between Rp51.000-Rp 100.000.The level of farmer losses average about 0-35% of normal production, and a decrease in average production of about Rp0 - Rp1 million of normal production. The results of multiple linear regression analysis showed that the variables of education, occupation, number of dependents, land prices and land area affect the willingness to pay or Willingness To Pay (WTP) mitigation of agricultural land prone to flooding in Purworejo.   Abstrak: Upaya studi ini bertujuan mengidentifikasi lokasi wilayah rawan banjir, mengetahui nilai ekonomi mitigasi lahan pertanian rawan banjir, dan mengetahui faktor-faktor yang mempengaruhi kesediaan membayar atau Willingness To Pay (WTP) mitigasi lahan pertanian rawan banjir di Kabupaten Purworejo. Data yang digunakan adalah data primer yang dilakukan dengan wawancara langsung kepada para responden. Teknik pengambilan sampel dengan menggunakan simple random sampling. Sampel dalam studi ini adalah 81 petani di Desa Kedungmulyo. Analisis data menggunakan Sistem Informasi Geografi (SIG), Contingent Valuation Method (CVM) dan regresi linier berganda. Hasil studi ini menunjukkan bahwa hampir semua kecamatan yang ada di Kabupaten Purworejo rawan banjir kecuali Kecamatan Bruno dan Kecamatan Kaligesing. Rata-rata kesediaan membayar terhadap mitigasi lahan pertanian rawan banjir antara Rp51.000,00–Rp100.000,00. Tingkat kerugian petani rata-rata sekitar 0-35% dari produksi normal, dan penurunan produksi rata-rata sekitar Rp0–Rp1.000.000,00 dari produksi normal. Hasil analisis regresi linier berganda menunjukkan bahwa variabel pendidikan, pekerjaan, jumlah tanggungan keluarga, harga lahan dan luas lahan berpengaruh terhadap kesediaan membayar atau Willingness To Pay (WTP) mitigasi lahan pertanian rawan banjir di Kabupaten Purworejo.